PUSAT PELATIHAN KARAKTER UNTUK MILENIAL - Venessa Handiwinata; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2019)
Millennial generation is the generation of births around 1980 to 2000 and in productive age. This generation has a problem, where they tend to be lazy, out of focus and narcissistic. There are 4 factors that cause it. First, this generation becomes depressed when in the workforce because there is no help from their parents and does not get what they want; second, this generation requires an addiction to the response of social media, which causes the absence of relations that improve between individuals; third, they do not last long in a company because they do not get what they want and want everything to be instant (inpatient); fourth, environmental participation that creates character of the individuals, where the environment at this time is more concerned with numbers than a community needs and only focus on short-term needs. In addition, the companies where they work don’t help/provide facilities to build cooperation and character development skills. Of all these problems, the millennial generation needs a facilities to develop their social skills, which can improve their ability to develop visions related to the development of their potential and innovation. Therefore, they need a character training center, with supporting facilities such as foodhall, shared work space, and gym facilities, where those supporting facilities can help the process of character training. This character training center has a concept that prioritizes togetherness and sociability with the